Modelling and Seismic Response Analysis of Existing URM Structures. Part 2: Archetypes of Italian Historical Buildings. Issue 7 (19th May 2023) - Lagomarsino, Sergio; Cattari, Serena; Angiolilli, Michele; Bracchi, Stefano; Rota, Maria; Penna, Andrea
ABSTRACT: This work presents a comprehensive strategy for analysing the complex seismic response of five Italian historical URM buildings, corresponding to different periods until 1920s. One distinctive feature of historical buildings is the need for integrating global modelling and local response of structural portions, due to possible activation of local failure modes interacting with the overall dynamic building response. Global behaviour is analysed via pushover and dynamic analyses of 3D equivalent-frame models. An original approach is adopted for assessing local out-of-plane mechanisms, accounting for their dynamic response to input time histories, filtered by the global response of the 3D model.